“El rol de los padres de familia en el proceso de enseñanza aprendizaje” - Moreno Romero, Verónica Yadira (2022)
Today education is the reflection of teamwork between family and school, since they have shared responsibilities for the correct pedagogical process of the student. The development of the student's potential and cognitive abilities is prioritized in the educational and social field. That is why, the intervention of the family in the teaching-learning process transcends the academic level that the child has. Indeed, the absence of parents in the educational process of their children generates a low academic performance in the student, because it presents difficulties in the development of school activities. In other words, the type of work and the level of economic income on the part of the parents generate a limited time in the responsibilities that they must fulfill with their children. The present investigative work aims to strengthen the participation of the role of parents, through the life history for the improvement of the teaching-learning process of the students. The methodology used is based on the interpretive paradigm, since it allowed us to understand the reality of the educational and social context of the research subject. Also, the types of research such as: qualitative, action, descriptive and bibliographical were used because relevant and pertinent findings of the school-family relationship were obtained. Together, the applied method was the inductive since there were several hypotheses to obtain different perceptions, the technique used was the interview and its instrument: interview guide, applied to the parent, teacher and authority of the institution. The result is a life story, which makes it possible to raise awareness of the role that the father plays in education and that, despite their work activities, they must dedicate time to share with their children. Likewise, it will raise awareness of the active participation of parents in the teaching-learning process of their representatives through the dissemination of this narrative, parents or legal representatives and teachers will reflect on the shared responsibilities that each one has for the correct development of the child in the educational and social context.